Introduction of Endovascular Thrombectomy to The Island Nation — The Maldives - Niyaf, Ali; Niraula, Kiran; Haaish Hashmath, Mohamed; Reeath Hameed, Mariyam; Bhattarai, Robin (Eastern Green Neurosurgery, 2024)
Over the years multiple treatment trials were researched up on for acute management of ischemic stroke to reduce mortality risk and morbidity rate among adults who suffered. Here, we report a case of 63 years Muslim diabetic female with multiple co-morbidities of coronary heart disease, pulmonary disease, and internal carotid artery aneurysm presented with thrombotic occlusion of left middle cerebral artery who underwent Maldives first ever endovascular thrombectomy using combined technique.